2002
DOI: 10.1002/hed.10094
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of clinically stage I and II oral tongue carcinoma—A comparative study of stage, thickness, shape, growth pattern, invasive front malignancy grading, martinez‐gimeno score, and pathologic features

Abstract: Tumor thickness should be considered in the management planning of patients with early oral tongue carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
175
3
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(196 citation statements)
references
References 31 publications
11
175
3
7
Order By: Relevance
“…Occult metastasis to neck in our cases was 13.5 % in contrast to conventional SCC cases which shows minimum of 30 % occult metastasis even in early cases [8][9][10].…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Occult metastasis to neck in our cases was 13.5 % in contrast to conventional SCC cases which shows minimum of 30 % occult metastasis even in early cases [8][9][10].…”
Section: Discussioncontrasting
confidence: 61%
“…VC is associated with recurrence after repeated excision but seldom leads to death unless it dedifferentiates into much poor grade on recurrence. 5 year disease free survival of entire cohort of 101 patients of verrucous carcinoma in study by Rohan R Walvekar et al [14] was 77.6 %, whereas; among conventional SCC, stage I and stage II cancers correspond to similar prognosis [8][9][10].…”
Section: Discussionmentioning
confidence: 98%
“…Nodal metastasis has been considered a significant prognostic factor in oral cavity cancers and other head and neck malignancies [6,13,118,135]. Even when the tumor is small and considered to be an early stage, it is potentially aggressive and the incidence of neck node metastases is very high.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that clinical N0 necks have shown occult metastases in about 30% or higher, depending on the size, site of primary tumor and the histological diagnostic methods [21,118]. The great challenge that is being faced by the head and neck oncologists and surgeons is the correct identification of the subset of head and neck cancer patients, of which oral carcinoma constitutes about 30% [90], without micro metastases to the cervical lymph nodes.…”
Section: Justification Of the Studymentioning
confidence: 99%
See 1 more Smart Citation